1948
DOI: 10.1021/ed025p353
|View full text |Cite
|
Sign up to set email alerts
|

Anglomathics.

Abstract: The title of this paper was proposed to the writer with the explanation that it signifies "translating the sense of problems and relationships among factors into mathematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The secular instability of the secondary component of a W UMa type binary arises because they obtain the luminosity transferred from the primary component (Lucy & Wilson 1979;Hazlehurst 1985;Wang 1994). So it could be suggested that decrease in the period of V 781 Tau is caused by the contraction of the secondary component, then its shrinking velocity can be calculated from the decrease rate in the orbital period.…”
Section: Change In the Period And Explanationmentioning
confidence: 99%
“…The secular instability of the secondary component of a W UMa type binary arises because they obtain the luminosity transferred from the primary component (Lucy & Wilson 1979;Hazlehurst 1985;Wang 1994). So it could be suggested that decrease in the period of V 781 Tau is caused by the contraction of the secondary component, then its shrinking velocity can be calculated from the decrease rate in the orbital period.…”
Section: Change In the Period And Explanationmentioning
confidence: 99%
“…Note that Lx = 4, but only the range |x| ≤ 2.5 is shown. 100 2 × 50 meshpoints, ∆s = 0.5, R0 = 1.0 factor in understanding contact binaries (Hazlehurst 1985(Hazlehurst , 1996.…”
Section: Discussionmentioning
confidence: 99%
“…The initial entropy excess of the bubble is given by the parameter ∆s. [In all cases presented we take ∆s = 0.5, which corresponds to the value used by Hazlehurst (1985), who adopts units where the nondimensional specific entropy is larger by a factor of 5. We note that larger values of ∆s make the bubble rise faster, but we found that even for ∆s = 2 the motion remained subsonic.…”
Section: Initial and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Secular instability of the secondary component of a W UMa type contact binary arises as it obtains the luminosity transferred from the primary component (Lucy & Wilson 1979;Hazlehurst 1985;Wang 1994). Wang (1994) studied the interaction between the secondary and the common convective envelope in contact binaries, and suggested that the two subtypes of W UMa type binaries may be in two different states of thermal relaxation oscillation: in the W-subtypes, the secondary is shrinking; while in the A-subtypes, the secondary is swelling.…”
Section: Contraction Of the Secondary And Mass Transfermentioning
confidence: 99%